Digital Wallets in the Metaverse: A Blockchain-Based Approach to Enhance Payment Systems - Mouloud AFOULOUS; Ferreira da Silva, C. (Proceedings of the 1st Iberian Conference on Cybersecurity and Artificial Intelligence, 2025)
The metaverse, an expansive virtual realm, intertwines seamlessly with blockchain technology and digital wallets, revolutionizing the landscape of digital interactions. This research navigates the convergence of these domains - metaverse, blockchain technology and digital wallets -, particularly emphasizing the imperative to fortify the interoperability and efficiency of payment systems within this evolving landscape. In this dynamic metaverse, users immerse themselves in virtual experiences, transcending the boundaries of the physical world. Simultaneously, blockchain technology stands out for its decentralized architecture and cryptographic foundations, offering a transformative influence across industries. Digital wallets, as crucial components in this paradigm, facilitate seamless transactions and asset management. This study aims to decipher the intricate relationship between the metaverse, blockchain, and digital wallets. By delving into existing literature, it identifies nuanced gaps and challenges in current payment systems within virtual realms. The research sets forth a novel blockchain-based approach to fortify the security of digital wallets within the metaverse. The emphasis lies in integrating decentralized technologies to instil trust, transparency, and efficiency in virtual transactions. A meticulously designed project execution plan charts the course for the research journey over four years. The plan encapsulates a comprehensive exploration, including literature reviews, prototype design and development, usability studies, security assessments, and regulatory analyses. This endeavour aspires to contribute not only to a nuanced comprehension of the metaverse but also to offer innovative solutions for interoperable digital transactions. By developing a tangible, secure digital wallet prototype, the research aims to influence and elevate the landscape of digital transactions within virtual environments.